The Wealth of Lithuania: its Value and its Assessors - Marčinskas, Albinas; Galinienė, Birutė (Ekonomika, 2001)
The article deals with the problems of assessment of the actual value of Lithuania: wealth. The problems are usually caused by the methodological drawbacks in the assessment system of national wealth (the whole entity). the failure to meet the requirements of international standards and the confusion in the present system of wealth classification at micro and macro levels.The calculations of the value of national wealth are still carried out using the methods, which are employed in determining the balance value. and Lithuanian statistics handles only a part of the national wealth.The wealth evaluation systems the main element of which is wealth assessor himself. his professionalism, and the possibilities for its enhancement are analyzed too.Furthermore article presents a new system of continuous professional development (an outline has been worked out and approved of) and offers to prove that Lithuanian wealth assessors and certification procedure complies with international harmonious quality standards. It also suggests preparing from the acknowledgement of a certifying institution.